Peculiarities of inclusive education organization in Europe and Ukraine - Berehova, Mariya (ScienceRise: Pedagogical Education, 2020)
Providing the necessary corrective assistance to children with special educational needs is the most important task of educational institutions in the system of inclusive education in Ukraine and in the world. The article describes the features of organization of inclusive education in the countries of the world and Ukraine. The basic literature on the problem is analyzed and features of organization of inclusive education in researches of scientists are revealed. On the basis of literature analysis, the essence of the concept of inclusion is investigated. The functioning of inclusive education institutions in the world is analyzed and a brief description of the features of the organization of inclusive education in the world is given. The basic tendencies of development of inclusion and principles of its realization are characterized. Analyzing the results of the research and scientific positions of scientists, we identified the main trends in the development of inclusive education. Inclusion, as an educational concept, is constantly evolving and is important for policy and strategies to address the causes and consequences of discrimination, inequality and exclusion. Inclusive education is based on a concept that eliminates any discrimination against students with disabilities and creates good conditions for quality education, upbringing and development for such children. Educators and scholars, who introduce the foundations of inclusive education into modern schools, recognize that every child can fully learn, and certain characteristics of people with disabilities are worthy of respect and should be a source of educational work for all participants in the educational process. Inclusive education in the world has been developing very rapidly for many years, teaching children with psycho-physical development peculiarities is in accordance with the principles, established by scientists. For Ukraine, inclusive education is a pedagogical innovation and, at the same time, a requirement not only of time, but also since the ratification of the UN Convention on the Rights of Persons with Disabilities - one of the international obligations of the state